2015
DOI: 10.1175/jamc-d-15-0077.1
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric Tornadic Debris Signature Variability and Debris Fallout Signatures

Abstract: Values of polarimetric radar variables may vary substantially between and through tornadic debris signature (TDS) events. Tornadoes with higher intensity ratings are associated with higher average and extreme values of reflectivity factor at horizontal polarization ZHH and lower values of copolar cross-correlation coefficient ρhv. Although values of these variables often fluctuate through reported tornado life cycles, ZHH repeatably decreases and ρhv repeatably increases across the volume scan immediately foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Even though both weak and strong/violent tornadoes and TDS/no TDS pairs were sampled evenly, the TDS cases clearly represented a larger percentage of EF2+ cases. Similar results were found by Van Den Broeke (2015). Sixteen of the damage points were associated with convection produced by a squall-line/quasi-linear convective system (QLCS) per the definition by Trapp et al (2005), while the rest were various forms of supercell or hybrid convection containing a persistent independent mesocyclone (Doswell and Burgess 1993;Smith et al 2012).…”
Section: Methodssupporting
confidence: 69%
See 3 more Smart Citations
“…Even though both weak and strong/violent tornadoes and TDS/no TDS pairs were sampled evenly, the TDS cases clearly represented a larger percentage of EF2+ cases. Similar results were found by Van Den Broeke (2015). Sixteen of the damage points were associated with convection produced by a squall-line/quasi-linear convective system (QLCS) per the definition by Trapp et al (2005), while the rest were various forms of supercell or hybrid convection containing a persistent independent mesocyclone (Doswell and Burgess 1993;Smith et al 2012).…”
Section: Methodssupporting
confidence: 69%
“…The IBW system differentiates tornado events by weak and strong/violent events. This guidance is built off of decades of science, but focuses on recent work quantifying the relationship between tornado damage intensity and subjectively analyzed WSR-88D volumetric products-specifically V rot (Kingfield and LaDue 2015;Smith et al 2015) and TDS height (Entremont and Lamb 2015;Van Den Broeke and Jauernic 2014). This study, evaluating 432 surveyed damage points from 84 different tornadoes, finds that the guidance is skillful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Van Den Broeke and Jauernic (2014) and Van Den Broeke (2015) catalogued TDS instances and their patterns nationwide using the criteria mentioned above. Using Dual-pol Radar data, Van Den Broeke and Jauernic (2014) found that 16% of the 1284 tornado cases they examined had TDS's associated with them.…”
Section: Introductionmentioning
confidence: 99%